ANALYSIS OF URBAN ECONOMIC SUSTAINABILITY IN VARANASI CITY (International Journal of Food and Nutritional Sciences, 2022)
Urban development should be guided by a sustainable planning and management vision that promotes interconnected green space, a multi-modal transportation system, and mixed-use development. Diverse public and private partnerships should be used to create sustainable and liveable communities that protect historic, cultural, and environmental resources. In addition, policymakers, regulators and developers should support sustainable planning and construction techniques that reduce pollution and create a balance between built and natural systems.Socio-economic development is any program that creates sustainable economic access for its beneficiaries. This means that contributions should be providing sustainable benefits, to use the old saying- teach people. Sustainable socio-economic development is a core element while studying the concept of urban sustainability. While the first part of this definition relates to conventional social and economic development objectives, the second part incorporates a long-term view, including considering environmental issues. It has become common to isolate four factors that determine sustainable development: natural capital (i.e., ecology), physical or produced capital, human capital and, more recently, social capital. This chapter is about basic civic amenities and infrastructure provided by the city authority to the urban people and raises several issues and constraints.